Fiscal federalism and public inputs provision: vertical externalities matter - Diego Martínez-López (European Central Bank (ECB), 2005)
This paper studies the provision of public inputs in a federal system. A vertical tax externality is also considered in a simple general equilibrium model used to analyze the efficiency of equilibria under different scenarios. The results show that the state provision of public inputs may affect ambiguously federal tax revenues, depending on the vertical tax externality, amongst others issues. Moreover, it is proved that achieving a second best allocation is not straightforward for a federal government that plays as Stackelberg leader. At this point, the state's reaction function becomes crucial when the design of vertical grants is restricted.
Keywords: H2; H4; H7; 330; Fiscal federalism; productive public spending; vertical externality; Finanzbeziehungen; Finanzausgleich; Allokationseffizienz; Steuerwirkung; Theorie